Designing CoFe2O4/Cellulose@L‐aspargine‐Co Nanocomposite: An Ultra‐Efficient Recyclable Catalyst in the Quick Reduction of Nitro Compounds under Eco‐Friendly Conditions. Issue 7 (15th February 2021) - Sorkhabi, Serve; Ghadermazi, Mohammad; Mozafari, Roya
Abstract: In this work, novel magnetic nanoparticles CoFe2 O4 /MCC (microcrystalline cellulose) @L‐aspargine‐Co have been synthesized via simple procedure and have been fully characterized using several techniques such as scanning electron microscopy (FE‐SEM), transmission electron microscopy (TEM), energy‐dispersive X‐ray spectroscopy (EDX), X‐ray atomic mapping, powder X‐ray diffraction (XRD), Fourier transform spectroscopy infrared (FT‐IR) and coupled plasma optical emission spectrometry (ICP‐OES). The catalytic efficiency of this nanocatalyst has been examined in the eco‐friendly reduction of different substituted nitro compounds to corresponding amines with sodium borohydride (NaBH4 ). The reactions were conducted in water at room temperature with high turnover numbers (TON) and turnover frequencies (TOF). The nontoxic nature, green reaction conditions, short reaction times, simple work‐up method and elimination of by‐products are some advantages of this approach. This organometallic catalyst was successfully recycled for eight times without losing the catalytic efficiency. Abstract : In this study, CoFe2 O4 /cellulose@L‐aspargine‐Co magnetic nanocatalyst was prepared as a recoverable and commercially available nanocatalyst by Co‐precipitation method and was fully characterized by different methods. Then the heterogeneous catalyst efficiently used for promotion the reduction of nitro compounds. The chief merits realized for this system were the operational simplicity, facile work‐up procedure, obtaining excellent yields and being done under green conditions. The catalyst could be easily isolated from the reaction mixture and reused several runs without appreciable loss in its efficiency.